2021
DOI: 10.1590/s1980-220x2020002003713
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and academic satisfaction of nursing students in traditional and integrated curricula

Abstract: Objective: To verify the prevalence of burnout and its relationship with the academic satisfaction of nursing students in traditional and integrated curricula. Method: Quantitative, observational, cross-sectional, and analytical descriptive study with nursing undergraduates in two public universities. The data were collected in the classroom through a characterization survey, Maslach Burnout Inventory, and the Nursing Student Satisfaction Scale, and analyzed through inferential and descriptive statistics. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(53 reference statements)
0
5
1
3
Order By: Relevance
“…Other factors found to be related to burnout were the quality and flexibility of learning, and the problems that may arise from these considerations ( 34 , 40 , 45 ). Thus, the better the learning experience, the greater the flexibility and the fewer problems that arise, the lower the degree of burnout experienced by these students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors found to be related to burnout were the quality and flexibility of learning, and the problems that may arise from these considerations ( 34 , 40 , 45 ). Thus, the better the learning experience, the greater the flexibility and the fewer problems that arise, the lower the degree of burnout experienced by these students.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the better the learning experience, the greater the flexibility and the fewer problems that arise, the lower the degree of burnout experienced by these students. Dissatisfaction with the academic course or with the practicum, the perception of a poor teaching environment or organization, or problems with the performance of theoretical or practical classes, all tend to aggravate burnout ( 25 , 30 , 34 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that burnout is rising among nursing students as they struggle to cope with stress in academic and clinical environments 7,8. Previous authors have found that 30% of undergraduate nursing students had symptoms of burnout syndrome,9 with 97.8% at a moderate risk for developing burnout 10. Nursing student burnout is a significant issue that leads to decreased academic success, increased attrition, and poor clinical performance 11–13…”
mentioning
confidence: 99%
“…(89) Outro estudo feito com residentes de pediatria mostrou que incorporar TBL no currículo de pediatria levou a grandes ganhos de conhecimento em curto prazo, mas que não persistiram a longo prazo. (90) Assim, a retenção do conhecimento varia de acordo com a metodologia utilizada.…”
Section: Conhecimento E Retenção De Conhecimentounclassified